Experimental manipulation of humidity in a cavity-nesting bird influences ectoparasites' abundance. Issue 4 (19th April 2022) - Castaño-Vázquez, F.; Merino, S.; Valera, F.; Veiga, J.
Abstract: Abstract: Climate change effects on host–parasite interactions have been poorly studied in arid or semi-arid habitats. Here, we conducted an experiment aimed to increase the temperature inside European roller Coracias garrulus nest boxes located in a semi-arid habitat on different nest-site types to look for effects on different ectoparasite abundances and nestling growth. Average nest temperature was slightly higher in heated nests than in control nests, although differences were not statistically significant. However, relative humidity was significantly lower at night in heated nests as compared to control nests. The abundance of sand flies, mites and carnid flies was significantly higher in heated, less humid, nests while biting midge abundance was significantly lower in heated nests. Other ectoparasites were not significantly affected by treatment. Relative humidity was high even in heated nests, reaching more than 60%. Sand fly abundance was higher in nests located in sandstone walls, while mite abundance was higher in isolated farmhouses. In addition, sand fly prevalence was higher in nests located in isolated farmhouses and sandstone walls. Heat treatment, nest-site type or ectoparasite abundances did not affect the nestling body mass, wing length or their growth at different nestling ages.